Assessment of the German and Italian stress cardiomyopathy score for risk stratification for in-hospital complications in patients with takotsubo syndrome - Santoro, Francesco; El-Battrawy, Ibrahim; Akın, Ibrahim (JAMA cardiology, 2019)
Importance: Takotsubo syndrome (TTS) is an acute, reversible heart failure syndrome featured by significant rates of in-hospital complications. There is a lack of data for risk stratification during hospitalization. Objective: To derive a simple clinical score for risk prediction of in-hospital complications among patients with TTS. Design, Setting, and Participants: In this prognostic study, 1007 consecutive patients were enrolled in the German and Italian Stress Cardiomyopathy (GEIST) registry from July 1, 2007, through December 31, 2017, and identified as the derivation cohort; 946 patients were enrolled in the Spanish Registry for Takotsubo Cardiomyopathy (RETAKO) as the external score validation. An admission risk score was developed using a stepwise multivariable regression analysis from 2 registries. Data analysis was performed from March 1, 2018, through July 31, 2018. Main Outcomes and Measures: In-hospital complications were defined as death, pulmonary edema, need for invasive ventilation, and cardiogenic shock. Four variables were identified as independent predictors of in-hospital complications and were used for the score: male sex, history of neurologic disorder, right ventricular involvement, and left ventricular ejection fraction (LVEF). Results: Of the 1007 patients enrolled in the GEIST registry, 107 (10.6%) were male, with mean (SD) age of 69.8 (11.4) years. Overall rate of in-hospital complications was 23.3% (235 of 1007) (death, 4.0%; pulmonary edema, 5.8%; invasive ventilation, 6.4%; and cardiogenic shock, 9.1%). The GEIST prognosis score was derived by providing 20 points each for male sex and history of neurologic disorders and 30 points for right ventricular involvement and then subtracting the value in percent of LVEF (decimal values between 0.15 and 0.70). Score accuracy on area under the receiver operating characteristic curve analysis was 0.71, with a negative predictive power of 87% with scores less than 20. External validation in the RETAKO population (124 [13.1%] male; mean [SD] age, 69.5 [14.9] years) revealed an area under the curve of 0.73 (P = .46 vs GEIST derivation cohort). Stratification into 3 risk groups (<20, 20-40, and >40 points) classified 316 patients (40.9%) as having low risk; 342 (44.3%) as having intermediate risk, and 114 (14.8%) as having high risk of complications. The observed in-hospital complication rates were 12.7% for low-risk patients, 23.4% for intermediate-risk patients, and 58.8% for high-risk patients (P < .001 for trend). After 2.6 years of follow-up, patients with in-hospital complications had significantly higher rates of mortality than those without complications (40% vs 10%, P = .01). Conclusions and Relevance: The GEIST prognostic score may be useful in early risk stratification for TTS. High-risk patients with TTS may require an intensive care unit stay, and low-risk patients with TTS could be discharged within a few days. In-hospital complications in patients with TTS may be associated with increased risk of long-term mortality.